Effects of Heat Treatment Processing on the Microstructure and Mechanical Properties of ZL114A Aluminum Alloy - KANG Fu-wei; LI Ru-yi; QIAO Xin; ZHANG Ji-min; FAN De-zhi (Journal of Harbin University of Science and Technology)
In order to study the effects of heat treatment on microstructure and properties of ZL114A aluminum alloy, microstructure observation and mechanical properties test of ZL114A aluminum alloy after different heat treatment were investigated by optical microscope, scanning electron microscope (SEM), transmission electron microscope (TEM), and tensile testing machine The results show that, with the increasing of the solution temperature from 505℃ to 550℃, fuse, spheroidization and coarsening phenomenon occurred in eutectic silicon of ZL114A alloy, hardness, tensile strength and elongation were increased, reached the maximum value at 535℃/12h, 897HB, 280MPa and 66%, respectively At the solution temperature 550℃, because grain become coarse and arise overburnt feature, the hardness and tensile strength decreased dramatically Therefore, suitable for the solution process is 535℃/12h The solution treated ZL114A alloy was aged at various temperature for 6h, the results show that with the increase of aging temperature from 140℃ to 170℃, the tensile strength increased from 286MPa to 345MPa, while the elongation decreased from 62% to 40% At 155℃, the tensile strength and elongation were 315MPa and 52%, respectively Comparing with ascasting ZL114A alloy, the tensile strength increased by 81%, and elongation increased by 108% According to the actual demand of the enterprise, the optimum heat treatment process is 535℃/12h +155℃/6h